Content validation of a questionnaire on healthcare personnel's perceptions of technologies - Maritza Díaz Rincón; Paula Constanza Arango Franco; Jose Alejandro Vergel Torrado; Olga Lucia Lora Díaz (Revista Cuidarte)
Introduction: Across the world, multiple institutions in the health sector actively promote the adoption and expansion of health technology innovations, driven by their potential benefits in improving medical care quality. The successful integration of health technologies into healthcare settings brings significant changes to work activities and depends, in part, on their acceptance and appropriation by healthcare personnel. Objective: To determine the content validity of a questionnaire adapted to assess perceptions and attitudes toward health technologies. Materials and Methods: Content validity was assessed through expert judgment using the model proposed by Escobar and Cuervo (2008). A 28-item questionnaire was adapted to assess health personnel's perceptions and attitudes toward technologies, and content validity was determined using Aiken's V coefficient. The Brennan and Prediger coefficient was used to assess agreement among experts. Results: The Aiken V coefficient was 0.98 (95% CI: 0.88 - 1.00) for the entire instrument. The expert agreement was almost perfect. Discussion: Most of the studies evaluating perceptions and attitudes toward technologies do not include validation through expert judgment before conducting statistical validation. Conclusions: According to the criteria of the consulted experts, the questionnaire's content validity is acceptable for assessing perceptions and attitudes toward health technologies.